Policy Analysis of Scout Extracurricular Programs in the Independent Curriculum toward the students' patriotic behavior at SMPN 4 Kemuning District, Indragiri Hilir Regency - Surahman, Dedi (Perspektif Pendidikan dan Keguruan, 2022)
This research aims to analyze the policy of the Scout extracurricular program on the behavior of loving the homeland of students at SMPN 4 Kemuning District, Indragiri Hilir Regency. The approach used in this research is a qualitative approach with descriptive research type. The subjects in this research were Class VII and Class VIII students, one Deputy Head of Student Affairs, one student council coach, and two scout coaches. The method of collecting information uses observation and interview methods which are then analyzed with information reduction sessions, information presentation, and drawing conclusions. The results of the research prove that scouting extracurricular activities in improving the behavior of loving the homeland there are 3 activities in the form of mutual cooperation activities, camping, and adventuring. In mutual cooperation activities students are taught to have the character of helping friends together to sterilize the area, on the contrary in camping activities students are required to maintain cleanliness when carrying out camping activities, and in adventurous activities students are required to always maintain nature so that it is not damaged. It can be concluded that by making habits to maintain the surrounding area or natural area so that it is always clean in mutual cooperation activities, camping activities and adventurous activities, the behavior obtained by students illustrates the behavior of loving the homeland towards the existing area. So that students can optimize patriotic behavior, students should be assisted by scout coaches to train themselves in scouting activities so that the activities carried out have a positive impact on students, especially in developing patriotic behavior.